2020
DOI: 10.3390/atmos11040392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sources and Trends in Agricultural GHG Emissions from Annex I Countries

Abstract: The vast majority of the scientific community believe that anthropogenic greenhouse gas (GHG) emissions are the predominant cause of climate change. One of the GHG emission sources is agriculture. Following the International Panel on Climate Change (IPCC) guidelines regarding GHG emission calculation, agriculture is responsible for around 10% of the overall global emissions. Agricultural GHG emissions consist of several emission source categories and several GHGs. In this article were described the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Pradhan and Limmeechokchai [27] reported that the GHG emission from Thailand agricultural sector in 2015 was estimated to be 45. These agricultural GHGs emissions originate from soil management, enteric fermentation, energy use, and manure management [28]. In descending order of magnitude, methane (CH4), nitrous oxide(N2O), and carbon dioxide(CO2) are the primary GHGs related to AFOLU [20].…”
Section: Afolu and Ghg Emissionsmentioning
confidence: 99%
“…Pradhan and Limmeechokchai [27] reported that the GHG emission from Thailand agricultural sector in 2015 was estimated to be 45. These agricultural GHGs emissions originate from soil management, enteric fermentation, energy use, and manure management [28]. In descending order of magnitude, methane (CH4), nitrous oxide(N2O), and carbon dioxide(CO2) are the primary GHGs related to AFOLU [20].…”
Section: Afolu and Ghg Emissionsmentioning
confidence: 99%
“…The climate-neutral economy to be achieved by 2050 requires substantial cuts in greenhouse gas (GHG) emissions in several sectors, including agriculture. Within agriculture, the most relevant sources of GHG are agricultural soils and enteric fermentation, with cattle standing as the most contributing livestock species [ 1 ]. Reducing animal farming GHG emissions requires broad, cohesive, and strategic plans.…”
Section: Introductionmentioning
confidence: 99%
“…Animals are typically categorized by species because the type of digestive system significantly influences CH 4 emissions. Ruminant species such as cattle are the main source of CH 4 emissions due to their intensive food fermentation [14]. CH 4 emissions from manure management are usually lower than those from enteric fermentation [15].…”
Section: Introductionmentioning
confidence: 99%
“…As estimated emissions are directly proportional to the cattle population (emission = emission factor × number of cattle) [14], the countries with the highest cattle population are the primary contributors to methane emissions from agricultural sources. The main regions for cattle production are South and North America, as well as Southeastern Asia.…”
Section: Introductionmentioning
confidence: 99%